Outcomes of Biliointestinal Bypass among Iranian Obese Patients - Naeini, Seyed Morteza Mousavi; Khalaj, Alireza; Abbaszadeh-Kasbi, Ali; Miri, Seyed Rouhollah (The Surgery Journal, 2018)
Background There are several surgical approaches to treat obesity not cured with medical approaches. Each method has its advantages and complications. In here, we have conducted a study to evaluate complications of biliointestinal bypass surgery (BIBP).Methods A prospective study was conducted in a private hospital from 2002 to 2016. Those patients, not previously operated for morbid obesity, were eligible. Mean follow-up period was 89 months ( ± 54 months; range: 73–108 months). Main outcome measures were weight, BMI (body mass index), concentrations of blood lipids and glucose, liver transaminases, and obesity-related comorbidities and complications.Results Twenty-three consecutive patients with morbid obesity, including 16 women (69.7%) and seven men (31.3%) with mean age 38.47 ± 10 years (range: 26–57 years) underwent surgery. At the end of follow-up period, a mean BMI reduction of 12.2 kg/m2 kg/m2 (p < 0.001)] was observed. An excess weight loss (EWL) of 63% ( ± 34) was achieved at the end of the study. Additionally, total cholesterol and triglyceride levels decreased postoperative significantly. The main long-term complications were flatulence (60%), borborygmus (47.8%), mal odorous stool (30.4%), and diarrhea (21.7%). Revision rate was 4.34%. There were no cases with irreversible hepatic injury, deaths due to the surgery, or progressive renal failure.Conclusion BIBP seems to be a safe, easily reversible, and one of valid therapeutic approaches in morbidly obese patients. BIBP has the potential to achieve durable weight loss and offers an improved quality of life.
Keywords: obesity; BIBP; efficacy; outcome